Reasons against audit exemption among SME companies in Malaysia - Cheng, Wei Kei; Beh, Chien Woon; Lim, Sok May; Teoh, Yet Yi; Thong, Joo Mei (2019)
According to Companies Act 2016 which has been newly implemented on 31st January 2017, SME companies are qualified for audit exemption. Therefore this study is to examine the factors against audit exemption among SME companies in Malaysia. By applying Agency Theory, the independent variables of this study will be size of the firm, agency factor, management factor and confidence level of third party. This study will provide significance information to SME companies in order to help them to decide whether they should demand for voluntary audit. Moreover, this study would be useful for future researcher as the confidence level of third party is the additional independent variable in our research model. The proposed study is designed to be a cross-sectional study by using primary data collection method to collect data from SME companies. Multi-stage cluster sampling technique is used to select the sample from SME Malaysia. Self-administered questionnaire is distributed in order to achieve the minimum sample size of 200 cases. Descriptive study will be used to describe the characteristic of our sample. Reliability, normality test, Pearson’s Correlation Coefficient test and Multiple Linear Regression analysis will be conducted to test for the hypotheses in this study. The result show that agency factor (AF), management factor (MF) and confidence level of third party (CL) have a significant relationship with voluntary audit (VA) while size of firm (SF) do not have significant relationship with voluntary audit (VA). This study would be able to useful for SME companies to decide whether their company need to be voluntary audit or not by providing them the importance and reasons for voluntary audit.